BAHAYA SAMPAH PLASTIK DI LAUT BAGI MAHLUK HIDUP - Muhammad Yatzin Azharil; Immanuel Paskah (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Abstract Plastic pollutes our planet and harms the oceans, endangering human health and destroying ecosystems that are essential to our livelihoods. Our oceans have faced serious threats from marine debris, also known as